Quantification of dsDNA functionalization efficiency in THz biosensors - Weisenstein, C.; Schmeck, M.; Schaar, Dominik; Wigger, A. K.; Boßerhoff, Anja Katrin; Bolivar, P. Haring (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2019)
In the past, THz bioanalytical techniques have been proven to be viable tools for label-free detection of biomolecules. However, significant improvements in the detection limit are needed to apply THz biosensors in biomedical diagnosis. To determine detection limits of the biosensor and the absolute amount of sample volume, quantitative measurements are required. We present label-free THz sensing of dsDNA and implement an approach based on reference investigations to quantify the dsDNA functionalization density. Defined functionalization densities are vital to maximize the adsorption of a dsDNA groove-binding protein, which acts as a tumor marker for malignant melanoma.
CRIS-Team Scopus Importer:2019-11-19